Classification of land for its use capability and conservation requirements - Moormann, F.R. (1978)
The intensification of agriculture on land used for shifting cultivation requires in most cases a thorough knowledge of the edaphlc and other attributes of such land* Modern techniques such as mechanization, higher-yielding varieties and the use of fertilizers can transform the extensive form of land use under shifting cultivation to a more intensive one with a considerably higher agricultural output per unit area. Introduction of such techniques can, however, lead to failure if soil conditions are not suitable or if other environmental factors are adverse. Many examples of failure to use shifting cultivation land for a high input, temperate zone type of agriculture can be cited from various countries in the lowland tropics. Determination of correct intensified land use thus requires a study in depth of the land and evaluation of factors which are limiting in view of such intensification.